Pedagogical Innovation in Statistics Teaching and Learning Using 5I’s Framework with Teachers and Teacher Educators: An Action Research Study - Sam Ol Kong; Seng Set; Chanphearun Sam (Scientia Publica Media, 2026)
This action research study sought to investigate how the implementation of the 5I’s pedagogical framework (Impress, Identify, Inspire, Inspect, Invoke) facilitates pedagogical innovation in statistics teaching and learning among teacher educators and teachers enrolled in a Master of Education program at Phnom Penh Teacher Education College (PTEC). The research employed a mixed-methods study, addressed the historical legacy of teacher-centered, rote-learning approaches in teaching and learning, and gathered data from participants over the course of a 15-week intervention using conceptual understanding pre- and post-test assessments, attitude surveys, and reflective learning logs. The Quantitative data were compared using paired samples t-tests with effect sizes calculated using Cohen’s d and inferential statistics, while survey responses were analyzed using descriptive statistics and Wilcoxon signed-rank tests. Qualitative data were analyzed using a combination of deductive and inductive approaches. The results demonstrated statistically significant improvements in conceptual understanding and positive shifts in interest, beliefs, and self-efficacy. While the qualitative analysis revealed transformative learning experiences characterized by emotional transitions from anxiety to agency, enhanced professional relevance, and the development of statistical habits of mind. The study illuminates how the 5I’s framework serves as a catalyst for pedagogical change by providing a structured yet flexible model that reconciles traditional Cambodian educational values with contemporary constructivist approaches. Findings also contribute to understanding how contextually responsive pedagogical innovations can facilitate meaningful pedagogical change in statistics teaching and learning within the Cambodian context, effectively enhancing conceptual understanding, fostering interest, and transforming beliefs about statistics among Cambodian teachers and teacher educators.